The Credibility of Reviews and Responses on Transaction Safety with a Dual Approach: Protecting Customer Transactions during the Covid-19 Pandemic - Januar Eko Aryansah; Muhammad Nur Budiyanto; Annada Nasyaya; Putri Uzdah Wulandari; Safa Anggreta (Indonesian Association for Public Administration (IAPA), 2022)
The establishment of the transaction safety program with the spirit of change made Bank Syariah Indonesia (BSI) gain widespread raising attention. This is evident from the author's observations and interviews with bank employees regarding the age range of the customer, which is 5-80 years. As a result, the author questions “what lies behind” the extremely high level of public confidence in the bank. It turned out that this occurred as a result of BSI using webform and BSI Mobile as transaction tools. This is what the BSI version of the transaction safety program means. The change made is very significant by switching the transaction system from a paper-based to a paperless one. Through a dual approach of Critical Discourse Analysis (CDA) and corpus linguistics, 100 comments were collected from the BSI Mobile application on the Play Store. In addition, interviews with BSI customers and direct observations of nearby BSI branches were carried out. The study's findings suggest that BSI's transaction safety program is a digital-based system that includes a website called the BSI webform and an application called BSI Mobile. By implementing a learning-by-doing system and ensuring perfect digital transaction systems, safety transactions are developed and put into practice. The program is routinely upgrading applications and websites and there is online learning about the system that has been upgraded. Therefore, bank employees must be adaptable to provide maximum service.